A study of user profiles and patterns in the Gonzalez Hall internet access centers - Garcia, Richard V. (2000)
Internet Access Centers provide online access on a fixed time for a fee. These centers connect online information and services to people that do not own the necessary hardware or cannot financially maintain an Internet account. However, online access centers established in or in connection with academic libraries, like the Institute of Library Science's Online Access Center; and the University of the Philippines Main Library's CyberNook and General Reference Section Access Centers, also have overall goal of supplying information in support of the University's various curricula as well as upgrading its facilities to cope with various client demands. The study collected information on the profiles and patterns of people who are drawn to the Internet and have used Access Centers situated inside the U.P. Main Library. The data collected was used to recommend measures for the enhancement of Internet use in these Access Centers.